2019
DOI: 10.3390/f10090777
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Top Soil Drought Hardly Affects Water Use of Picea abies and Larix decidua Saplings at the Treeline in the Austrian Alps

Abstract: This study quantified the effect of shallow soil water availability on sap flow density (Qs) of 4.9 ± 1.5 m tall Picea abies and Larix decidua saplings at treeline in the Central Tyrolean Alps, Austria. We installed a transparent roof construction around three P. abies and three L. decidua saplings to prevent precipitation from reaching the soil surface without notably influencing the above ground microclimate. Three additional saplings from each species served as controls in the absence of any manipulation. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…In addition to our experiment on mature trees, we performed a drought experiment on saplings of L. decidua and P. abies growing in an open gap adjacent to our study site composed only of young trees, where precipitation was excluded during the same treatment periods. In contrast to what we found for mature trees, tree growth and the water use of saplings of both species was largely unaffected by the drought treatment (Wieser et al, 2019). This supports the notion that mature trees have a lower drought acclimation capacity than young and small trees (Fajardo et al, 2019; Olson et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to our experiment on mature trees, we performed a drought experiment on saplings of L. decidua and P. abies growing in an open gap adjacent to our study site composed only of young trees, where precipitation was excluded during the same treatment periods. In contrast to what we found for mature trees, tree growth and the water use of saplings of both species was largely unaffected by the drought treatment (Wieser et al, 2019). This supports the notion that mature trees have a lower drought acclimation capacity than young and small trees (Fajardo et al, 2019; Olson et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…Oberhuber et al [11] analyzed the growth trends of conifers along environmental transects in the Central European Alps and explain the missing adequate growth response to climate warming, competition for resources in increasingly denser stands at subalpine sites, and by frost desiccation injuries of evergreen tree species at the Krummholz-limit. Wieser et al [12] investigated the effects of artificial topsoil drought on the water use of Picea abies and Larix decidua Mill. saplings at the treeline in the Austrian Alps.…”
mentioning
confidence: 99%
“…However, experimental studies on the effects of top-soil drought indicated that three years of rain exclusion did not considerably reduce sap flow density of P. abies and L. decidua saplings at the treeline in the Stubai Valley. The lack of a significant sap flow-soil water content correlation in both tree species indicated sufficient water supply, suggesting that whole tree water loss of young trees at the treeline primarily depends on evaporative demand [40]. Furthermore, roots of the treeline-associated conifers are able to penetrate into rocky undergrounds, allowing for the utilization of water sources in deep and wet soil layers, as shown for L. decidua trees using hydrogen stable isotope analysis [107].…”
Section: Water Relationsmentioning
confidence: 89%
“…In-situ manipulative warming and rain shelter experiments are common methodologies for assessing the effects of rapid climate change [35]. They can be quite effective in simulating climate warming [36][37][38][39] and top soil drought [40,41] in high elevation forests. Compared to the space-for-time approach, such techniques provide an explicit control in simulating climate warming or artificial soil drought.…”
mentioning
confidence: 99%